Efektifitas Amniotic Membrane Sebagai Dressing Penyembuhan Luka Bakar Pada Tikus Putih (Rattus Norvegicus) - Ratna Widyawati; Desty Apritya (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
This study aimed to determine the effectiveness of the speed the healing of burns used amniotic membrane by propolis and propolis amniotic membrane without white rats (Rattus norvegicus). This study was an experimental study with the technique of sampling by completely randomized design. The variables measured were the speed of healing old wounds and wound healing time (days). This study used 30 rats were divided into 4 groups. The group (P1) as a negative control, the White Rat (Rattus norvegicus) wrapped in sterile gauze, group (P2) as a positive control, the White Rat (Rattus norvegicus) by betadine and wrapped in sterile gauze. The group (P3) Rats (Rattus norvegicus) wrapped with amniotic membrane + sterile gauze and groups (P4) Rats (Rattus norvegicus) + propolis + + gauze sterile amniotic membrane. The result showed that Speeds healing of burns negative kontrol, PI and P2 there are differences, also between PI and P2. Between control positive and PI showed not difference. It can show from some indications that include wet or dryness of the wound, whether there is swelling in the wound, the wound color (red or white), linkage outskirts of injuries, whether there is a scab, and the open or closed wounds, but the long time healing wounds (day) are different, PI and kontrol positive are the best result, they are nine days.